2017
DOI: 10.1021/acs.nanolett.6b04971
|View full text |Cite
|
Sign up to set email alerts
|

Accommodating High Transformation Strains in Battery Electrodes via the Formation of Nanoscale Intermediate Phases: Operando Investigation of Olivine NaFePO4

Abstract: Virtually all intercalation compounds exhibit significant changes in unit cell volume as the working ion concentration varies. NaFePO (0 < x < 1, NFP) olivine, of interest as a cathode for sodium-ion batteries, is a model for topotactic, high-strain systems as it exhibits one of the largest discontinuous volume changes (∼17% by volume) during its first-order transition between two otherwise isostructural phases. Using synchrotron radiation powder X-ray diffraction (PXD) and pair distribution function (PDF) ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 42 publications
9
67
0
Order By: Relevance
“…Similar intermediate loss of crystallinity has also been observed in other systems, e.g. NaFePO 4 [19]. In the case of extraction of two Li-ions, the full crystallinity is regained after a full charge-discharge cycle, while ~2% crystallinity appears to be lost after having extracted and re-inserted three Li-ions.…”
Section: Dynamic Charge-discharge Phase Evolutionsupporting
confidence: 79%
“…Similar intermediate loss of crystallinity has also been observed in other systems, e.g. NaFePO 4 [19]. In the case of extraction of two Li-ions, the full crystallinity is regained after a full charge-discharge cycle, while ~2% crystallinity appears to be lost after having extracted and re-inserted three Li-ions.…”
Section: Dynamic Charge-discharge Phase Evolutionsupporting
confidence: 79%
“…However, a variety of structure-sensitive techniques of high spatial resolution (such as those used in the work reported by Xiang et al 10 ) that probe local electrode microstructure are often less informative for tracking structural changes in the composite electrodes on a mesoscopic scale. This inspired us to choose LFP and NFP composite electrodes (with commonly used poly(vinylidene fluoride) [PVdF] binder) cycled in both aqueous and non-aqueous electrolyte solutions for a quantitative study of the mechanical electrode/binder interactions using an electrochemical quartz crystal microbalance with dissipation monitoring (EQCM-D).…”
Section: Context and Scalementioning
confidence: 99%
“…9 It was recently suggested that the large lattice mismatch between the NFP and FP phases can be mitigated, thereby accommodating the high strain of the lattice, by the formation of an intermediate amorphous phase giving rise to an initial stage of a plastic deformation in NFP electrodes. 10 For more than a 3-fold lower transformation strain in LFP electrodes, the extent of the active mass amorphization is negligibly small. In turn, important and intensively studied Li-Si anodes undergo much more pronounced volume expansion upon lithiation, and the transformation strain thus developed is 20-fold larger in comparison with that for NFP.…”
Section: Introductionmentioning
confidence: 99%
“…Using synchrotron XRD and PDF analysis, Xiang et al investigated the strain accommodation mechanism in NaFePO 4 , which possesses the largest known transformation strain ( ∼17 vol%) in the olivine compounds [131] . A new strain-accommodation mechanism was revealed, that the large lattice mismatch between the two end members NaFePO 4 and FePO 4 is alleviated by formation of a third, amorphous phase.…”
Section: The Application Of Synchrotron Pair Distribution Function (Pdf)mentioning
confidence: 99%